2021
DOI: 10.1071/fp20159
|View full text |Cite
|
Sign up to set email alerts
|

Role of antioxidant pool in management of ozone stress through soil nitrogen amendments in two cultivars of a tropical legume

Abstract: The present experiment was done on two different cultivars of a tropical legume, Cymopsis tetragonoloba L. Taub. (cluster bean) cvv. Pusa-Naubahar (PUSA-N) and Selection-151 (S-151). The experiment was conducted under ambient ozone (O3) conditions with inputs of three different doses of inorganic nitrogen (N1, recommended; N2, 1.5-times recommended and N3, 2-times recommended) as well as control plants. The objective of this study was to evaluate the effectiveness of soil nitrogen amendments in management of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Out of the two varieties of Dolichos lablab L. exposed to ambient and elevated O 3 concentrations, Kashi Sheetal had higher endogenously generated H 2 O 2 in its control leaves as compared to Kashi Harittima, as evident through the histochemical assay of H 2 O 2 localization (Figure 4). Related findings have reported that cultivars with higher levels of endogenous H 2 O 2 are more tolerant than cultivars with lower levels of H 2 O 2 (Caregnato et al, 2013;Yadav et al, 2019;Gupta and Tiwari, 2020). Caregnato et al (2013) reported significantly higher H 2 O 2 localization in the leaves of two varieties of Phaseolus vulgaris L. grown in EO 3 conditions in comparison to AO 3 conditions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Out of the two varieties of Dolichos lablab L. exposed to ambient and elevated O 3 concentrations, Kashi Sheetal had higher endogenously generated H 2 O 2 in its control leaves as compared to Kashi Harittima, as evident through the histochemical assay of H 2 O 2 localization (Figure 4). Related findings have reported that cultivars with higher levels of endogenous H 2 O 2 are more tolerant than cultivars with lower levels of H 2 O 2 (Caregnato et al, 2013;Yadav et al, 2019;Gupta and Tiwari, 2020). Caregnato et al (2013) reported significantly higher H 2 O 2 localization in the leaves of two varieties of Phaseolus vulgaris L. grown in EO 3 conditions in comparison to AO 3 conditions.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that H 2 O 2 was produced in the leaves of Cymopsis tetragonoloba L. Taub. (Cluster bean) was significantly decreased with increasing nitrogen amendment doses (Gupta and Tiwari, 2020). It is suggested that the surplus nitrogen available to the plant gets allocated to improve the antioxidative potential of the plants which results in improved scavenging of the H 2 O 2 (Podda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the discrepancy of enzymatic response at different developmental stages in EO 1 and EO 2 plants can be well-correlated to the respective ROS contents. Whereas SOD catalyses the dismutation of O 2 −0 and H 2 O 2 , APX and CAT are responsible for scavenging H 2 O 2 [ 18 , 71 , 72 ]. Non-significant variations in O 2 −0 accompanied by an increase in H 2 O 2 contents demonstrate the rapid activity of SOD.…”
Section: Discussionmentioning
confidence: 99%
“…NOx levels in India showed an annual increasing trend of 0.9 ppb from 2010 to 2015 [ 8 ]. In India, the middle Indo-Gangetic Plains have seen high concentrations in the last few years, as made evident by a number of studies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%